Rancang Bangun Aplikasi Bank Sampah Berbasis Mobile dengan Pendekatan Gamifikasi: Studi Kasus: Kelurahan Cipameungpeuk, Kabupaten Sumedang - Deni Andayani; Agun Guntara; Yanyan Sofiyan (Repeater : Publikasi Teknik Informatika dan Jaringan, 2026)
Waste management at the community level in Indonesia faces a persistent challenge: low household participation in waste sorting, compounded by manual administrative systems in waste bank operations. This study aimed to design and develop a gamification-based mobile application, SampahKu, to support waste bank operations at Kelurahan Cipameungpeuk, Sumedang. The application was built using the Flutter framework with Firebase as backend infrastructure and integrated three gamification elements points, badges, and leaderboard grounded in the Octalysis Framework and Self-Determination Theory (SDT). Development followed an Agile/Scrum methodology across iterative sprints. Functional evaluation was conducted through Black Box Testing (BBT) on 15 test scenarios, achieving a 100% pass rate. User Acceptance Testing (UAT) was carried out with five purposively selected participants (three residents and two waste bank officers) through a Likert-scale questionnaire on five dimensions: point system, badges, leaderboard, motivation, and ease of use. Overall UAT score reached 94% (very acceptable category). While these results indicate that users positively perceived the gamification elements after a brief trial session, the study acknowledges that this does not constitute proof of sustained behavioral change. Longitudinal evaluation with a larger sample is needed to validate long-term motivational impact. This study contributes a theoretically grounded gamification design model for community-level environmental applications in Indonesia.